1986
DOI: 10.1002/chin.198636201
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Trifluoromethylsulphonyl Derivatives of Benzofuroxanes and Their Anionic o‐Complexes.

Abstract: The synthesis of the benzofuroxanes (IIIa) and (IIIb) is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…11,12 Experimental Materials 4-Nitro-6-trifluoromethylsulfonylbenzofuroxan 5 (mp 176 ЊC, lit. 25 181 ЊC) was prepared from the thermal decomposition of the corresponding substituted phenyl azide in toluene. 25,26 Cyclopentadiene obtained from the heating of bicyclopentadiene was used without further purification.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 Experimental Materials 4-Nitro-6-trifluoromethylsulfonylbenzofuroxan 5 (mp 176 ЊC, lit. 25 181 ЊC) was prepared from the thermal decomposition of the corresponding substituted phenyl azide in toluene. 25,26 Cyclopentadiene obtained from the heating of bicyclopentadiene was used without further purification.…”
Section: Resultsmentioning
confidence: 99%
“…Electron-withdrawing groups in molecules are prerequisite for enabling a variety of transformations in organic chemistry, including processes proceeding via carbanionic intermediates, nucleophilic substitutions, elimination reactions, and so forth , Yet, in recent years, other structural moieties have been explored with the possibility of rivalling, or even exceeding, the electron-withdrawing capability of NO 2 . One avenue of approach, developed since the 1960s by Yagupol'skii and by Sheppard, was through modification of the sulfonyl (SO 2 )R group via electron-withdrawing substituents as in SO 2 CF 3 . In turn, these novel substituents have found utility in different realms of chemistry. …”
Section: Introductionmentioning
confidence: 99%
“…Inasmuch as there is a direct relationship between the electronic mode of action and the acidifying effect of a substituent, it is a noteworthy feature that the literature contains a number of conflicting reports regarding the relative electron-withdrawing effects of the SO 2 CF 3 and NO 2 groups. On the basis of the p K a values of 4-X- and 3-X-substituted benzoic acidsthe conventional reference in Hammett's scaleYagupolskii and Sheppard have found that SO 2 CF 3 is notably more electron-withdrawing than a NO 2 group: σ m = 0.76 and σ p = 0.96 for X = SO 2 CF 3 ; σ m = 0.74 and σ p = 0.78 for X = NO 2 . , The SO 2 CF 3 group was also reported to be more activating than a NO 2 group in nucleophilic aromatic substitutions and related σ-adduct formation processes. , However, in contrast with these results, Bordwell has reported that ((trifluoromethyl)sulfonyl)methane is 1.5 p K a units less acidic than nitromethane in Me 2 SO solution . A similar p K a difference is observed in comparing unsubstituted benzyltriflone (C 6 H 5 CH 2 SO 2 CF 3 ) to phenylnitromethane (C 6 H 5 CH 2 NO 2 ) in the same solvent. , On the other hand, it has been reported that CH 3 SO 2 CF 3 is 7 p K units more acidic than CH 3 NO 2 in the gas phase, in contrast with the generally observed situation that acidities in the gas phase and Me 2 SO follow a similar order …”
mentioning
confidence: 99%